Production of Bacterial β-Galactosidase Using Wastes of Dairy Industry - Safaa Salah El-Din Taha; Osama Abd El-Hamid Ibrahim; Einas Hamed El-Shatoury; Amany Mohamed El-Deeb; Hayam Abd El-Naby Sayed (Novel Research in Microbiology Journal)
UF-Cheese permeate is a dairy byproduct characterized by high lactose content, generated through the ultrafiltration process that separates proteins and fats from milk. The aim of this study was to use UF-Cheese permeate as a medium for promoting bacterial growth to producing the β-galactosidase (lactase) enzyme, which is beneficial for individuals with lactose intolerance in manufactured dairy products. Lactic acid bacteria, also known as LAB are recognized as effective producers of the lactase enzyme. A total of eleven LAB isolates were evaluated for their ability to produce intracellular lactase in a submerged fermentation setup under static conditions. Among the isolates that demonstrated positive results, the most prolific lactase producer was identified as Lactiplantibacillus plantarum strain S1 through 16S rDNA sequencing. The assay of β-galactosidase production was performed using O-nitrophenyl β-D-galactopyranoside (ONPG) as a hydrolytic substrate. Improvement of β-galactosidase synthesis from the selected Lactiplantibacillus plantarum strain S1, utilizing permeate as a growth medium, was achieved through the application of response surface methodology. A peak β-galactosidase activity of 5.523 U/ ml was recorded at a pH 7, a lactose concentration of 4.6 %, UF-cheese permeate serving as a carbon source, 2 % potassium nitrate (KNO₃) as a nitrogen source, an inoculum size of 5%, and incubated at 37 ºC for 24 h. In this study, the UF-cheese permeate as a dairy waste, considered an environmental pollution, was used as a fermentation substrate for functional microorganisms such as LAB, offering a promising alternative for waste management and sustainable production of high-quality metabolites, including enzymes, mainly proteases and β-galactosidase, organic acids, exopolysaccharides (EPSs), and bacteriocins. This is in addition to isolating a novel lactic acid bacterial strain identified as Lactiplantibacillus plantarum strain S1, which displayed the potential to generate β-galactosidase when cultivated on UV-cheese permeate as a fermentation medium. The obtained β-galactosidase enzyme had the capacity to facilitate the substantial manufacturing of low-lactose dairy products tailored for individuals with lactose intolerance. This enzyme has diverse applications in food, pharmaceuticals, agriculture, and biofuels. This suggests that a bacterial strain may not only have a capacity for enzyme production but also operates efficiently, representing a promising candidate for further studies and potential applications in the biotechnological processes.